The Russian Military's New 'Main Emphasis': Asymmetric Warfare. Issue 4 (4th July 2017) - Thornton, Rod
Abstract: The nature of the Russian military threat to Western interests needs to be reassessed. An examination of articles in Russian military journals shows that its senior ranks now see 'asymmetric means and methods' as their new 'main emphasis' in modern peer-state wars. Rod Thornton explains that for them, winning such wars through asymmetric means has become a key way to impose Moscow's will on other states. Remarkably, they seek to avoid the use of military violence.